2020
DOI: 10.1159/000505744
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Dissociations among Phonological Processing Skills, Language Skills and Nonverbal Cognition in Individuals with Autism Spectrum Disorder

Abstract: <b><i>Aims:</i></b> The purpose of this study was to examine the nature of phonological processing in individuals with autism spectrum disorder (ASD) as it pertains to their nonverbal cognitive and linguistic abilities. <b><i>Methods:</i></b> Twenty-one participants between the ages of 9 and 21 years were administered a nonverbal cognitive assessment (Raven test), a language measure that requires receptive and expressive knowledge of semantics, syntax and morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…As the performance of predictive skills presents an interdependent relationship, it is important that professionals working in the context of individuals with ASD, including speech therapists, teachers, psychologists, and educators, are aware of and attentive not only to phonological awareness, but also to another reading-related skill, which is phonological memory because it works together with phonological awareness in learning to read (2,29,58) . Some methodological limitations of this review should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…As the performance of predictive skills presents an interdependent relationship, it is important that professionals working in the context of individuals with ASD, including speech therapists, teachers, psychologists, and educators, are aware of and attentive not only to phonological awareness, but also to another reading-related skill, which is phonological memory because it works together with phonological awareness in learning to read (2,29,58) . Some methodological limitations of this review should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported household income (Jyotishi et al, 2017; Kover et al, 2014). As for non-specific indicators, Jokel et al (2021) reported that participant SES was “mid to high” without further details. Barbaro and Dissanayake (2012) used the Socio-Economic Index for Areas (Australian Bureau of Statistics, 2018), which is a compound measure including neighborhood- but not participant-level indices: relative SES disadvantage, SES advantage and disadvantage, economic resources, and education and occupation.…”
Section: Resultsmentioning
confidence: 99%
“…percentage of parents with a bachelor’s degree or higher). Two studies reported descriptive text (Jokel et al, 2021; Jyotishi et al, 2017). These differing descriptors of SES give rise to two considerations.…”
Section: Resultsmentioning
confidence: 99%
“…The supramarginal gyrus was studied and associated with phonological processing and verbal working memory [ 43 ], also its activation was shown to relate to higher expressive language [ 44 ]. The defect of voice memory is a characteristic of people with ASD and might affect their language acquisition [ 45 ]. The radial unit hypothesis proposes that the expansion of cortical surface area is driven by the proliferation of neural progenitor cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%